Do backers prefer crowdfunding or pre-order? An empirical study - Zhou, Yuan; Cui, Jie; Wang, Nianxin (Frontiers in Psychology, 2022)
To advertise or estimate demand, many pre-order items appear on crowdfunding platforms. Few studies have explored backers’ preferences between crowdfunding projects and pre-order items. To analyze backers’ preferences, 1,800 technology and innovation campaigns were collected from the Indiegogo crowdfunding platform. Using the product stage badge, the campaigns in the concept and prototype stages were treated as crowdfunding projects, while those in the production and shipping stages were labeled pre-order items, resulting in 1,305 crowdfunding projects and 495 pre-order items, respectively. Propensity score matching was leveraged to investigate differences in fundraising outcomes between crowdfunding projects and pre-order items. The results indicate that pre-order items have better fundraising outcomes than crowdfunding projects, suggesting that backers are risk-averse on the crowdfunding platform.